2009
DOI: 10.2466/pms.108.2.383-391
|View full text |Cite
|
Sign up to set email alerts
|

Goal Priming and Self-Efficacy: Independent Contributions to Motor Performance

Abstract: It is well-established that goal pursuit and performance are responsive to the goal characteristics (e.g., difficulty, specificity) and beliefs about self and the task (e.g., self-efficacy). Also, contextual factors may lead to nonconscious goal activation and pursuit. Nevertheless, much remains to be discoverd concerning the way conscious and nonconscious goals are related. In this study, the way in which self-efficacy and nonconscious goal priming may affect a goal-directed activity was explored. 67 right-ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…In sum, self-efficacy, optimism, hope and resiliency are related to EP (Nguyen et al, 2011). 1) Self-efficacy has been found to have a positive impact on EP Legal & Meyer, 2009).…”
Section: Psychological Capitalmentioning
confidence: 99%
“…In sum, self-efficacy, optimism, hope and resiliency are related to EP (Nguyen et al, 2011). 1) Self-efficacy has been found to have a positive impact on EP Legal & Meyer, 2009).…”
Section: Psychological Capitalmentioning
confidence: 99%
“…When participants pursued the conscious monitoring goal and the nonconscious detection goal, priming had a positive effect on detection. Such positive effects of the interplay of compatible conscious and nonconscious goals on performance were previously obtained and can be explained by the motivational processes triggered by the priming manipulation (e.g., Bargh et al, 2001;Hassin, Aarts et al, 2009;Hassin, Bargh et al, 2009;Légal & Meyer, 2009). It can also explain why the detection goal priming improved performance in the monitoring task as well as the detection of the unexpected event.…”
Section: Discussionmentioning
confidence: 58%
“…Interestingly, it was demonstrated that nonconscious goal pursuit is flexible (Hassin, Aarts, Eitam, Custers, & Kleiman, 2009) and can run in parallel to a conscious activity. Thus, conscious and nonconscious goals can coexist, especially when both types of goals are compatible or share a high degree of similarity (e.g., Bargh et al, 2001;Hassin, Aarts et al, 2009;Hassin, Bargh et al, 2009;Légal & Meyer, 2009). In that case, nonconscious and conscious goal pursuits would make use of the same underlying motivational circuits and systems (Huang & Bargh, 2014) and lead to improved performance.…”
Section: Goal Primingmentioning
confidence: 99%
“…We speculate that while the patients with CSPI may not have maintained the position sense improvements around midrange, they may have moved away from the end-range postures, 7 potentially reducing spinal tissue loading, 24 thereby reducing pain and disability. 61 Future research examining participants' perceptions and knowledge about postural interventions would be useful to explore how the experimental conditions interact with the participants' beliefs and goals. This may have had a powerful effect on patients' cognitions, beliefs, expectations, and self-effi cacy, which in turn may have infl uenced their pain and perceived disability levels.…”
Section: Discussionmentioning
confidence: 99%